Development of nanoscale biosensors for cancer related proteases and blood-borne pathogens based on electrochemical and optical methods - Swisher, Luxi Zhang (Kansas State University, 2015)
A lot of materials exhibit novel properties when scaled down to nanoscale. Here we explore nanoelectrode arrays (NEAs) and nanoparticles in the application of high performance biosensors. We have developed an electrochemical (EC) method for measuring the activity of proteases using vertically aligned carbon nanofiber (VACNF) NEAs. VACNFs were grown on conductive substrates and encapsulated in SiO₂ matrix. After polishing and plasma etching, controlled VACNF tips are exposed to form an embedded NEA. Tetrapeptides specific to cancer-mediated proteases are covalently attached to the exposed tip, with a ferrocene (Fc) moiety linked at the distal end. The redox signal of Fc can be measured with AC voltammetry (ACV) at ~1 kHz frequency, showing distinct properties from macro-electrodes due to VACNF's unique interior structure. The enhanced ACV properties enable the kinetic measurements of proteolytic cleavage of the surface-attached tetrapeptides by proteases. The well-defined regular VACNF NEAs by e-beam lithography show a much faster kinetics for cathepsin B proteolysis. This EC method was further applied in whole lysate of human breast tissue and breast cells. The detected protease activity was found increased in cancer cells, with the metastatic cancer cell lysate showing the highest cathepsin B activity. The results indicated the potential of this technique as a portable multiplex electronic device for cancer diagnosis and treatment monitoring through rapid profiling of the activity of specific cancer-relevant proteases. In another exploratory study, we modified nanoparticles with luminol and viral nucleic acid to develop chemiluminescence (CL) biosensors for blood-borne pathogens. Luminol-labeled 10-nm-diameter gold nanoparticles (GNPs) served as a nanocarrier for enhancing CL signal. The CL signal can be observed over 8 orders of magnitude variations in GNP concentration. Using the same number of particles, luminol-labeled 30-nm-diameter latex beads showed ~3 orders of magnitude higher CL compared to 10-nm-diameter GNPs. Hybridization of target H1N1 nucleic acid on the latex beads and probe nucleic acid on the glass or optical fiber surface has been achieved. This assay will be incorporated into a simple hand-held device for routine assays in hospitals and clinics, or for large-scale screening of human populations as diagnostic tools to identify specific viral strains.
Keywords: VACNFs; Protease; Chemiluminescence; DNAElectrochemistry; Chemistry (0485); Nanoscience (0565); Nanotechnology (0652)